Study on mechanical properties of concrete inclusion of high-volume coal bottom ash with the addition of fly ash - Abdul Muiz, Hasim; Khairul Anuar, Shahid; Nur Farhayu, Ariffin; Nurul Natasha, Nasrudin; Muhammad Nor Syahrul, Zaimi (Elsevier Ltd, 2022)
Coal bottom ash (CBA) has been widely utilized in concrete production as a partial replacement for aggregate. Still, the massive amount of CBA generated every day ends up dumped at a landfill without economic value. Therefore, the aim of the study identified the influence of CBA as a coarse and fine aggregate replacement, in addition of fly ash (FA) as a partial cement substitution in concrete made. The experimental tests were carried out on the fresh and hardened state of concrete to evaluate the workability test, compression test, flexural test, and modulus of elasticity test. CBA was replaced in concrete by four different combination arrangements between half (50%) and full (100%) coarse and fine aggregate using the volume replacement method. Then, 20% of FA was substituted to the mass of cement as an additive cementitious material to enhance the pozzolanic reaction. The results revealed that a high amount of CBA in concrete contributed to the low workability of fresh concrete. The concrete made by 100% CBA as coarse and fine aggregate replacement produced better compressive strength than the control concrete. Besides, all replacement levels of CBA in concrete had a modulus of elasticity in the range of 5.07 to 5.67 GPa, which is acceptable for its compression strength of 30 to 35 MPa at 28 days. Besides, CBA concrete recorded a significant reduction in flexural strength with the increment level of percentage CBA in concrete mix ingredients. Therefore, the evaluation of the mechanical properties of concrete containing large volume CBA with the addition of FA shows good performance and has the potential to be utilized in concrete manufacturing.